Modulation of the elasticity of single crystal, 1-D metal dimethylglyoximato complexes via solid solution effect. Issue 26 (6th June 2022) - Sugimoto, Akira; Kusumoto, Sotaro; Nakaya, Manabu; Sekine, Yoshihiro; Lindoy, Leonard F.; Hayami, Shinya
Abstract : Novel elastic crystals with metal complexes are reported. The flexibility of solid solution crystals of the complexes varies with the proportion of metal ions present in the crystals. Abstract : The fabrication of single crystal material with a desired degree of flexibility is a challenging topic in material science and crystal engineering. In this communication, we demonstrate the modulation of elasticity via a solid solution effect occurring in single crystals of one-dimensional, heterometal chain complexes.